Cell-mediated and humoral immune responses of cyprinids induced by a live attenuated vaccine against cyprinid herpesvirus 2 infection in comparison to the virus non-permissive high temperature water treatment - Hiroaki, Saito; Lau, Lik Ming; Shungo, Minami; Manami, Yuguchi; Megumi, Matsumoto; Teruyuki, Nakanishi; Hidehiro, Kondo; Goshi, Kato; Motohiko, Sano (Elsevier Ltd., 2024)
The live attenuated vaccine (P7-P8 strain) against cyprinid herpesvirus 2 (CyHV-2) infection of goldfish shows high protective efficacy. However, the underlying immune mechanism induced by P7-P8 vaccination remains unknown. It is known that the fish survived in the primary infection with CyHV-2 by the virus non-permissive high temperature (HT) water treatment elicit immunity against secondary virus challenge. In this study, the immunity induced by the P7-P8 vaccine was compared with that by HT treatment. To further explore the immunological responses of cyprinids, in addition to goldfish Carassius auratus, susceptible isogenic ginbuna C. auratus langsdorfii was included in this study. In the primary immune response, cyprinids were vaccinated with P7-P8, or treated with HT. In the secondary immune response, cyprinids were challenged with the virulent CyHV-2. The percentage dynamics of CD4-1 and CD8α positive lymphocytes were determined during the primary and secondary immune responses of the two cyprinids. Blood plasma was sampled to assess the anti-CyHV-2 IgM antibody titers. The vaccination with P7-P8 and HT-treatment induced high protection immunity in the cyprinids with relative percentage survival of over 88 % against virulent virus challenge. Our finding shows that the CD8α positive lymphocytes rather than CD4-1 positive lymphocytes play an important role in the secondary immune responses of cyprinids vaccinated with P7-P8. The CD4-1 positive lymphocytes rather than CD8α positive lymphocytes play an important role in the secondary immune responses of cyprinids treated with HT. The antibody titer of vaccinated cyprinids did not increase greatly even after virulent virus challenge. The results suggest the vaccine activates the CD8α cells and the secondary cell-mediated immunity. The differences in the induced immunity mechanisms in fish by the two measures might be based on the virus either being an avirulent virus form that cannot evade host responses or a virulent virus form that cannot propagate at non-permissive temperature.